(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The main features and difficulties of the process of attracting a loan for starting a business are analyzed. The ways of the broker’s participation in their solution are highlighted. The article describes the stages of interaction between credit brokers and entrepreneurs in the process of attracting loans for startups.